Comparison of intracortical inhibition and facilitation in distal and proximal arm muscles in humans - Abbruzzese, Giovanni (Blackwell Science Inc, 1999)
1. Cortico-cortical inhibition and facilitation induced by paired transcranial magnetic stimulation (TMS) of the human motor cortex were investigated in the distal muscle opponens pollicis (OP) and the proximal muscle biceps brachii (BB) of normal subjects. 2. The test response evoked by TMS (125 % of motor threshold, MTh) in the relaxed OP and BB muscles was inhibited by a conditioning TMS (80 % of MTh) at short interstimulus intervals (ISIs; 2-5 ms) and facilitated at longer ISIs (10-25 ms). The test response was significantly less inhibited at short ISIs and more facilitated at long ISIs in the BB than OP. 3. The MTh at rest was significantly lower for the OP than for the BB, indicating a greater excitability of OP cortical area. However, the above pattern of inhibition and facilitation was preserved both when the stimulus intensity was adjusted to evoke test responses of matched size in the two muscles and within an ample range of conditioning stimulus intensities. 4. The use of a circular coil or a focal figure-of-eight coil produced no qualitative differences in the pattern of inhibition and facilitation in either muscle. 5. The significant difference in MTh between muscles was lost during voluntary activation. In both muscles, pre-innervation abolished the cortico-cortical facilitation and reduced the cortico-cortical inhibition. However, the latter remained larger in the OP than BB muscle. 6. We suggest that the different potency of intracortical inhibitory and facilitatory circuits directed towards distal and proximal arm muscles is related to their diverse prevalent functions.